Accelerated habit formation following amphetamine exposure is reversed by D1, but enhanced by D2, receptor antagonists - Nelson, Andrew J.; Killcross, Simon (Frontiers in Neuroscience, 2013)
Repeated exposure to the psychostimulant amphetamine has been shown to disrupt goal-directed instrumental actions and promote the early and abnormal development of goal-insensitive habitual responding (Nelson and Killcross, 2006). To investigate the neuropharmacological specificity of this effect as well as restore goal-directed responding in animals with pre-training amphetamine exposure, animals were treated with the non-selective dopamine antagonist α-flupenthixol, the selective D1 antagonist SCH 23390 or the selective D2 antagonist eticlopride, prior to instrumental training (3 sessions). Subsequently, the reinforcer was paired with LiCL-induced gastric-malaise and animals were given a test of goal-sensitivity both in extinction and reacquisition. The effect of these dopaminergic antagonists on the sensitivity of lever press performance to outcome devaluation was assessed in animals with pre-training exposure to amphetamine (Experiments 1a-1c) or in non-sensitized animals (Experiment 2). Both α-flupenthixol and SCH23390 reversed accelerated habit formation following amphetamine sensitization. However, eticlopride appeared to enhance this effect and render instrumental performance compulsive as these animals were unable to inhibit responding both in extinction and reacquisition, even though a consumption test confirmed they had acquired an aversion to the reinforcer. These findings demonstrate that amphetamine induced-disruption of goal-directed behaviour is mediated by activity at distinct dopamine receptor subtypes and may represent a putative model of the neurochemical processes involved in the loss of voluntary control over behaviour.